Differenze nella colonizzazione di diversi substrati naturali in ambiente portuale - Canessa, Martina; Gaggero, Laura; Castelli, Filippo; Garaventa, Francesca; Piazza, Veronica; Bavestrello, Giorgio (Biologia Marina Mediterranea, 2025)
The physical and chemical properties of bedrock shape the structure and dynamics of benthic communities. The mutual contribution of mineral composition and grain size in conditioning the early stages of colonization of different rocky substrates was investigated in the Genoa harbour using 10x10 cm panels of marble, quartzite and slate in summer 2023. The main species found were Amphibalanus amphitrite, Hydroides elegans and Schizoporella errata. The number of organisms resulted maximal on slate and minimal on marble. The richness of the benthic community was inversely related to the mineral size, while the presence of quartz did not show an inhibitory effect. The ability to react differently in the presence of different silicate mineral structures depends on a complex of mechanisms involving the surface properties of the same mineral. Moreover, this selectivity can be activated/inhibited during different phases of the biological cycle.